1999
DOI: 10.1021/jp992405f
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Measurement Of the Ionization Energies and Cross Sections Of Uranium and Plutonium Oxide Vapors

Abstract: The ionization and dissociation energies of the different uranium and plutonium oxides have been measured by mass spectrometry of molecular beams produced by Knudsen effusion at high temperature. The values obtained constitute a set of self-consistent quantities, which are in agreement with the existing thermodynamic data of these oxides. On the basis of the experimental molecular parameters, general formulas for the ionization and dissociation/ionization cross sections due to electron inelastic scattering hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 24 publications
9
80
2
Order By: Relevance
“…The IE(PuO 2 ) = 6.36 eV computed by CASPT2+SO is in reasonably good agreement with the value of about 6.6 eV estimated by Capone et al 6 It is notable that previously reported values, which are in the range of 9-10 eV. 5,7 This conclusion is clearly validated by the present theoretical results. It should be noted that the discrepancy of 0.5 eV between the computed value of 6.4 eV and the lower limit of 6.9 eV 1 determined from the electron transfer reactions is minor relative to the large correction, >2 eV, to previously reported experimental 5,7 and theoretical 10 values.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The IE(PuO 2 ) = 6.36 eV computed by CASPT2+SO is in reasonably good agreement with the value of about 6.6 eV estimated by Capone et al 6 It is notable that previously reported values, which are in the range of 9-10 eV. 5,7 This conclusion is clearly validated by the present theoretical results. It should be noted that the discrepancy of 0.5 eV between the computed value of 6.4 eV and the lower limit of 6.9 eV 1 determined from the electron transfer reactions is minor relative to the large correction, >2 eV, to previously reported experimental 5,7 and theoretical 10 values.…”
Section: Resultssupporting
confidence: 92%
“…5,7 This conclusion is clearly validated by the present theoretical results. It should be noted that the discrepancy of 0.5 eV between the computed value of 6.4 eV and the lower limit of 6.9 eV 1 determined from the electron transfer reactions is minor relative to the large correction, >2 eV, to previously reported experimental 5,7 and theoretical 10 values.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The M/F ratios in each case consider the UO 2 and UO as two separate parent masses with U as the fragment mass in each case. This treatment of the data is used for simplicity and does not include the full complement of known fragmentation pathways for gas phase UO x molecules [29].…”
Section: Resultsmentioning
confidence: 99%
“…A joint effort of experimentalists and theoreticians is therefore needed to resolve the electronic structure of these systems. An example is the ionization potential ͑IP͒ of the UO 2 molecule, measured as 5.4 eV by Capone et al 2 using the electron impact technique. Theoretical calculations 3 consistently gave a higher value.…”
Section: Introductionmentioning
confidence: 99%